2017
DOI: 10.18494/sam.2017.1375
|View full text |Cite
|
Sign up to set email alerts
|

An Aqueous Ammonia Sensor Based on Printed Indium Tin Oxide Layer

Abstract: We proposed an indium tin oxide (ITO) sensor for detecting NH 3 in seawater and carried out a series of experiments to investigate the feasibility of using it as a hazardous and noxious substance (HNS) sensor. The ITO layer revealed a distinct resistance change, which was linearly correlated with the NH 3 concentration at room temperature. The ITO layer was evaluated using a seawater and ammonium hydroxide (NH 4 OH) solution. The evaluation revealed an almost linear output signal up to an NH 3 concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…(14) Films using ITO nanoparticles showed a higher chemical stability in water than those using other metal oxides. (15) Moreover, a recent result confirmed the capability of an ITO sensor to detect ethanol concentrations as low as 619 ppb. (12) However, according to existing research, the measurement time was tens of minutes or more and needed improvement.…”
Section: Introductionmentioning
confidence: 83%
“…(14) Films using ITO nanoparticles showed a higher chemical stability in water than those using other metal oxides. (15) Moreover, a recent result confirmed the capability of an ITO sensor to detect ethanol concentrations as low as 619 ppb. (12) However, according to existing research, the measurement time was tens of minutes or more and needed improvement.…”
Section: Introductionmentioning
confidence: 83%
“…3 Chang et al found that the porous structure of the screen-printed ITO layer is preferred for developing a highly sensitive ammonia sensor. 4 Yadav et al prepared the PITO films using a sol−gel spincoating method for the CO 2 gas sensor. The porous morphology was suggested to provide many sites to adsorb CO 2 molecules and improve the sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high electrical conductivity, transparency, and thermal stability, tin-doped In 2 O 3 (ITO) films have been widely used in information displays, electroluminescent devices, electrochromic devices, sensors, , solar cells, bioanalytical devices, , catalysis, etc. ITO incorporated with magnetism can also be used to make new magneto-optoelectronic devices. , The introduction of well-defined pores in ITO under retention of high conductivity and transparency brings the following advantages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation